PROGRAM-ORIENTED PLANNING IN RUSSIA AND ABROAD - R. Gavva (Publishing House of the State University of Management, 2017)
In article planning and management on the basis of development and implementation of the target state, federal, departmental programs financed from means of budgets of different levels and off-budget funds are considered. It is noted that they become the leading directions of increase in efficiency of functioning of economy and the social sphere in Russia and in other countries of the world community. The carried-out analysis showed that along with the general, universal principles and forms of application of program and target approach in planning, management, budgeting the originality of quantity, scales, ways of financing, the fields of use of social and economic programs in the different countries is observed.